Organoleptic Characteristics of Tempeh from Durian Seed (Durio zibethinus Murr) as Alternative Raw Material - Nuryanti, Siti; Rahmawati, Sitti; Magfirah, Magfirah; Sriyulaningsi, Sriyulaningsi (Postgraduate, University of Mataram, 2024)
Durian seeds have a high starch content, making it possible to be used as a raw material for making tempeh as an alternative to soybeans This research aims to make tempeh using durian seeds as raw material and determine the taste of durian seed tempeh using organoleptic tests. The method used to make tempeh from durian seeds is by fermentation, the durian seed samples are washed, cleaned, then boiled and the hard skin removed, then sliced and steamed until soft. The final stage of the two-day fermentation process continues with packaging. To determine suitability for consumption, an organoleptic/taste test (color, taste, texture and aroma) is carried out. The panelists who determined the taste consisted of several people from the Chemistry Study Program, FKIP UNTAD. The results of the study showed that durian seed tempeh was less white compared to soybean tempeh. The panelists' organoleptic tests for color liking levels stated that they liked 50% and disliked 50%, for taste 60% liked, liked 10% and disliked 30%, and texture panelists stated that they liked 60% and disliked 40% and 70% liked the aroma and 30% disliked it. The conclusion obtained in this research is that durian seeds can be used as an alternative for making tempeh and can reduce durian seed waste